The role of arts therapies in mitigating Sleep Initiation and Maintenance Disorders: a systematic review - Luo, Xuexing; Zhang, Aijia; Li, Hong; Li, Yu; Ying, Fangtian; Wang, Xiaoli; Yang, Qianxu; Zhang, Zheyu; Huang, Guanghui (Frontiers in Psychiatry, 2024)
Introduction Arts therapies offer effective non-pharmacological intervention for Sleep Initiation and Maintenance Disorders (SIMDs), encompassing both passive and active modalities. This review assesses their effectiveness and ethical considerations, focusing on music therapy, meditation, and Tai Chi. Methods Following PRISMA guidelines, a detailed search across PubMed, the Cochrane Library, Web of Science, and CNKI identified 17 relevant RCTs. Utilizing the Joanna Briggs Institute (JBI) quality criteria and the PICO(S) framework for data extraction ensured methodological integrity. Results Analysis shows arts therapies significantly improve sleep quality. Music therapy and meditation yield immediate benefits, while Tai Chi and Qigong require longer commitment for significant outcomes. Discussion The link between SIMDs and mental health issues like anxiety, stress, and depression suggests arts therapies not only enhance sleep quality but also address underlying mental health conditions. The evidence supports a wider adoption of arts therapies in treating SIMDs due to their dual benefits. Systematic review registration PROSPERO, ID: CRD42024506393.